In vitro analysis of lytic peptide to target breast and prostate cancer. - Riaz Jannoo (2015)
In the United Kingdom 1 in 3 will develop some form o f cancer during their lifetime. Despite the development o f new drugs and use o f combinational therapies, mortality rates have not improved. Between 1979 and 2008, incidence rates for cancer in the United Kingdom increased by 26% The second most common cause o f cancer deaths is prostate cancer in men and breast cancer in women, the first being lung cancer. Current methods for treating cancer involve radiation therapy and chemotherapy. However, resistance to these therapies is common.Targeting o f cell surface receptors specifically or over expressed in cancer cells has painted a new insight in anti-cancer therapy. The Gonadotropin-releasing hormone receptor (GnRHR), luteinizing hormone/choriogonadotropin receptor (LHCGR) and Interleukin-13 receptor alpha 2 (IL-13Ra2) are overexpressed in some human tumours, including prostate and breast cancer. IL-13, GnRH and PCG ligands bind to the cell surface receptors IL-13Ra2, GnRHR and LHCGR respectively.The gene expression o f GnRHR, LHCGR and IL-13Ra2 in a wide range o f human cancer tissues as well as in 2D cultured (monolayers) prostate and breast cancer cell lines was analysed. Their levels were shown to be overexpressed, indicating their potential use for diagnosis and targeting treatment.Unlike 2D monolayer cultures, 3D spheroid cultures achieve in vivo-like conditions in cancer. We therefore developed quick, easy and reproducible 3D tumour models o f prostate and breast cancer cell lines and used them to validate the cancers target ability for the lytic peptides.Both 2D monolayer and 3D spheroid cultures o f breast and prostate cancer cells overexpressing IL-13Ra2, GnRHR and LHCGR were targeted using Pep-1, [D-Trp6]GnRH and pCG(ala) peptides conjugated covalently to a membrane disrupting lytic peptide (Phor21). The lytic peptide drugs [D-Trp6]GnRH-Phor21, Pep-l-Phor21 and Phor21-pCG(ala) conjugates were shown to selectively kill prostate and breast cancer cells with their toxicity dependent on the expression levels o f the respective receptors at the cell surface.